Differing Tales of Two Patients after Receiving a Kidney Transplant from a Donor with Disseminated Intravascular Coagulation - Pradeep V. Kadambi; Ann K. Gamilla-Crudo; Mohammad Almiani; Michelle A. Josephson; W. James Chon (Case Reports in Transplantation)
In order to decrease the time on the deceased donor kidney wait list and to have more organs available, criteria for acceptable organs for transplant could be made less stringent. There are reports of successful recipient outcomes using kidney donors presenting with disseminated intravascular coagulation (DIC). We report a unique circumstance where two patients received kidneys from the same deceased donor who had DIC; one patient developed thrombotic microangiopathy (TMA) while the other did not. This difference in outcome may indicate that both donor and recipient factors contribute to the development of posttransplant TMA.